1984
DOI: 10.1002/crat.2170190606
|View full text |Cite
|
Sign up to set email alerts
|

Effect of impurities on dynamic dragging of dislocations

Abstract: In honour of Professor V. I. STARTSEV'S 70th birthday The rearrangement of the force of dynamic dragging of a dislocation due t o its elastic interaction with impnrity atoms is analysed. The collisions of a moving dislocation with impurities excite additional vibrations of a dislocation line. Such vibrations lead to tho appearance of extra parts to dissipative function and effective friction force of a dislocation which dcperid on location and concentration of impurities. This effect is one of tho reasons of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…Its boundaries are defined by the inequalities (bc/v) l L, if l L, and (bc/v) L l, if L l. In this range the drag force is not sensitive to the presence of spectrum gap, and, for the same in Ref. 7, it is inversely proportional to the dislocation velocity…”
Section: Model and Calculationmentioning
confidence: 95%
“…Its boundaries are defined by the inequalities (bc/v) l L, if l L, and (bc/v) L l, if L l. In this range the drag force is not sensitive to the presence of spectrum gap, and, for the same in Ref. 7, it is inversely proportional to the dislocation velocity…”
Section: Model and Calculationmentioning
confidence: 95%
“…when the dislocation kinetic energy is greater than the energy of dislocation interaction with the impurities YUob-lno, where U, is the energy of dislocation bonding to the impurity atom. According t o [4], for the centre of dilatation lJ, N p&. Making use of this expression rn x $2 ,pb2c;2 for the evaluation of the dislocation mass we obtain the applicability condition for our model in the form w > ct(no&)lI2.…”
Section: (21)mentioning
confidence: 95%
“…Here no is the dimensionless concentration of defects, no x nb3 (see [4]). At velocities v > v o = d/x the function @(x) ==x2 and the deceleration force is proportional to 1:-l which is in agreement with the results of [ 2 to 41.…”
Section: (I) O Z # ( P ) =mentioning
confidence: 99%
“…Additional features in the behavior of dislocations in crystals appear in the presence of a magnetic field (see [2][3][4]). The experiments show that the application of a magnetic field can noticeably change the plastic properties of crystals.…”
Section: Introductionmentioning
confidence: 99%
“…For example, under a simultaneous influence of a weak magnetic field and constant electric current in the case of silicon crystal deformation, a significant decrease of plasticity is detected [2]. In [3], it has been shown that the dynamic deceleration of dislocations takes place in the case of their movement in the metals under the presence of a magnetic field. In [4], the deformation fields in the blocks of an X-ray interferometer under the constant magnetic field is investigated.…”
Section: Introductionmentioning
confidence: 99%